Pengembangan Jobsheet Praktek Instalasi Perumahan Berbasis Trainer Langlois Tae 1-3 M - Pepen Agustin Putra; Fivia Eliza (Jurnal Pendidikan Teknik Elektro, 2022)
This research was carried out because in the lighting installation course there is no jobsheet on Tae Langlois 1-3 media, so this study aims to produce a jobsheet for Tae Langlois 1-3 media which is useful to support the learning of residential installation courses. The method in this study is the type of research and development R&D (research and development) using a 4D model, consisting of the define, design, develop and disseminate stages. The sample in this study were undergraduate students of electrical engineering, Faculty of Engineering, State University of Padang who had taken practical housing installation courses. Based on the results of the study, the validity data obtained from the three validators, namely the first lecturer was very valid, the second lecturer was very valid, and the third lecturer was valid. So, the results obtained from the three lecturers can be categorized as very valid. The practicality test will be conducted by a lecturer in the electrical engineering department and 20 electrical engineering students who have taken practical housing installation courses. The practicality questionnaire filled out by the lecturers was stated to be very practical and the results from the respondents were very practical. The effectiveness test was carried out by testing the material using the Langlois Tae 1-3M trainer for 4 meetings with 4 different materials with 10 student participants. From the three tests, it can be concluded that the Langlois Tae 1-3M trainer jobsheet is very valid, practical and effective to be used as a supporting job sheet for housing installation practicum courses.